2008
DOI: 10.1021/ef7007858
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Alkali Metals during Pyrolysis and Gasification of a Lignite

Abstract: Transformation of Na and K in a lignite was investigated during pyrolysis and gasification in a fixed-bed by using a serial dissolution method with H 2 O, CH 3 COONH 4 , and HCl solutions. The evolution of the fractions of four forms in solid and alkali volatilization during pyrolysis and gasification was determined. The results show that a different mode of occurrence between Na and of K in coal existed. Na in coal can be nearly completely dissolved by H 2 O, CH 3 COONH 4 , and HCl solution. However, K in coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 15 publications
(20 reference statements)
4
61
0
Order By: Relevance
“…The slight difference between two coals could result in different characteristics of sodium release during pyrolysis. With the increase of pyrolysis temperature from 700 to 900°C, the decrease of CH 3 COONH 4 -soluble Na and K was also reported by Wei et al 25 Quyn et al 38 indicated that sodium in the form of NaCl was more easily volatilized than that in the form of carboxylate in coals, which is consistent with the present results.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The slight difference between two coals could result in different characteristics of sodium release during pyrolysis. With the increase of pyrolysis temperature from 700 to 900°C, the decrease of CH 3 COONH 4 -soluble Na and K was also reported by Wei et al 25 Quyn et al 38 indicated that sodium in the form of NaCl was more easily volatilized than that in the form of carboxylate in coals, which is consistent with the present results.…”
Section: Resultssupporting
confidence: 92%
“…Wei et al 25 and Sugawara et al 14 also observed the increase trend of sodium volatility with increasing pyrolysis temperature. The volatilization ratios of sodium are 37% and 35% at 800°C for ZJ coal and WCW coal, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…This even more affirmed the possibilities of reactions R1 and R2 indicated above. Besides of the reaction R2 from CaO to Ca2Al2SiO7, CaSO4 was also proposed to react with SiO2 and Al2O3 to produce Ca2Al2SiO7 at around 800 o C [21].…”
Section: Figure 6 Residual Ash Morphologies At (A)-600 O C (B)-815 mentioning
confidence: 99%
“…20,32−35 The AAEM species in biomass and low-rank coal mainly exist in four different chemical forms: H 2 O-soluble forms (e.g., soluble salts), CH 3 COONH 4 -soluble forms (e.g., carboxylates), acid-soluble forms (e.g., silicates and aluminates), and stable form (e.g., covered by carbon and silico-aluminates). 36,37 Generally, AAEM species contain more-soluble salts and carboxylates than the other two chemical forms. The catalytic effects of AAEM species largely depend on their chemical form.…”
Section: Introductionmentioning
confidence: 99%